Cognitive functioning and clinical characteristics of children with non-syndromic orofacial clefts: A case-control study - Sándor-Bajusz, Kinga Amália; Dergez, Tímea; Molnár, Edit; Hadzsiev, Kinga; Till, Ágnes; Zsigmond, Anna; Vástyán, Attila; Csábi, Györgyi (Frontiers in Psychology, 2023)
The higher rate of neuropsychiatric disorders in individuals with non-syndromic oral clefts has been well documented by previous studies. Our goal was to identify children with non-syndromic oral clefts that are at risk for abnormal neurodevelopment by assessing their cognitive functioning. A single-center, case-controlled study was carried out at the Department of Pediatrics of the University of Pécs in Hungary. The study consisted of three phases including questionnaires and psychometric tools to assess IQ and executive functioning. Forty children with non-syndromic oral clefts and 43 age-matched controls participated in the study. Apgar score at five minutes was significantly lower for the cleft group (p=0.031), in addition to delays observed for potty-training (p=0.008) and speech development (p=0.039). Psychiatric disorders where more common in the cleft group (15%) than in controls (4.5%), but not significantly (p=0.143). The cleft group scored lower on the Continuous Performance Test (p=0.022). Subgroup analysis of the cleft group revealed significant relationships between parental socioeconomic status, overall academic average, IQ and speech and language therapy. Children with non-syndromic oral clefts seem to be at risk for deficits involving the attention domain of the executive system. These children additionally present with difficulties that affect cognitive and speech development. With time, children with non-syndromic oral clefts demonstrate similar cognitive strengths as their peers and show significant skill development. Longitudinal studies with larger sample sizes are needed to provide more conclusive evidence on cognitive deficits in children at risk for neurodevelopmental difficulties.